Takinib inhibits microglial M1 polarization and oxidative damage after subarachnoid hemorrhage by targeting TAK1-dependent NLRP3 inflammasome signaling pathway - Wang, Weihan; Pang, Cong; Zhang, Jiaxing; Peng, Lei; Zhang, Xianghua; Shi, Lin; Zhang, Hao (Frontiers in Immunology, 2023)
Transforming growth factor-β-activated kinase 1 (TAK1) positively regulates oxidative stress and inflammation in different diseases. Takinib, a novel and specific TAK1 inhibitor, has beneficial effects in a variety of disorders. However, the effects of takinib on early brain injury (EBI) after subarachnoid hemorrhage (SAH) and the underlying molecular mechanisms remain unknown. Our study showed that takinib administration significantly inhibited phosphorylated TAK1 expression after SAH. In addition, takinib suppressed M1 microglial polarization and promoted M2 microglial polarization. Furthermore, blockade of TAK1 by takinib reduced neuroinflammation, oxidative damage, brain edema, and neuronal apoptosis, and improved neurological behavior after SAH. Mechanistically, we revealed that TAK1 inhibition by takinib mitigated reactive oxygen species (ROS) production and ROS-mediated nod-like receptor pyrin domain-containing protein 3 (NLRP3) inflammasome activation. In contrast, NLRP3 activation by nigericin abated the neuroprotective effects of takinib against EBI after SAH. In general, our study demonstrated that takinib could protect against EBI by targeting TAK1-ROS-NLRP3 inflammasome signaling. Inhibition of TAK1 might be a promising option in the management of SAH.